Armed conflict, militarization and ecological footprint: Empirical evidence from South Asia. (25th January 2021) - Qayyum, Unbreen; Anjum, Sohail; Samina Sabir,
Abstract: Environmental degradation as a consequence of military activities largely remains a neglected subject, especially in South Asia. To fill this gap, we have investigated the impact of armed conflicts and militarization on the environmental dilapidation of South Asian countries from 1984 to 2019. A second generational unit root test has been applied to check the problem of cross-sectional dependency. Westerlund panel cointegration method is used to analyze the cointegration between selected variables. Long-run and short-run estimates have been calculated using the panel autoregressive distributed lag (ARDL) method. Besides, the Granger Causality test is employed and results indicate the causality runs from armed conflict and militarization to ecological footprint. Empirical estimates also confirm that the military expenditures, internal conflict as well as external conflict have a positive impact on ecological footprint and these results are highly significant both in the long run and short run. Our study also confirms the presence of the Environmental Kuznets Curve in South Asia. South Asia is marred by the aggressive posturing bitterness as witnessed by the sour relationship that exists between Pakistan and India, the two strongest nations in the region. This animosity left them with consistent and incremental growth in defense expenditure. To achieve sustainable development in South Asia it is imperative to initiate peace talks and to impose necessary restrictions on hazardous military operations contaminating the environment.